Striatal Cholinergic Neurotransmission Requires VGLUT3 - Nelson, Alexandra B. (Society for Neuroscience, 2014)
It is now clear that many neuronal populations release more than one classical neurotransmitter, yet in most cases the functional role of corelease is unknown. Striatal cholinergic interneurons release both glutamate and acetylcholine, and vesicular loading of glutamate has been shown to enhance acetylcholine content. Using a combination of optogenetics and whole-cell recordings in mice, we now provide physiological evidence that optogenetic stimulation of cholinergic interneurons triggers monosynaptic glutamate- and acetylcholine-mediated currents in striatal fast-spiking interneurons (FSIs), both of which depend on the expression of the vesicular glutamate transporter 3 (VGLUT3). In contrast to corticostriatal glutamatergic inputs onto FSIs, which are mediated primarily by AMPA-type glutamate receptors, glutamate release by cholinergic interneurons activates both AMPA- and NMDA-type glutamate receptors, suggesting a unique role for these inputs in the modulation of FSI activity. Importantly, we find that the loss of VGLUT3 not only markedly attenuates glutamatergic and cholinergic inputs on FSIs, but also significantly decreases disynaptic GABAergic input onto medium spiny neurons (MSNs), the major output neurons of the striatum. Our data demonstrate that VGLUT3 is required for normal cholinergic signaling onto FSIs, as well as for acetylcholine-dependent disynaptic inhibition of MSNs. Thus, by supporting fast glutamatergic transmission as well as by modulating the strength of cholinergic signaling, VGLUT3 has the capacity to exert widespread influence on the striatal network.